Undergraduate students' evaluation and reflections on a gerodontology programme. (28th May 2018) - Attard, N.; Schembri, A.; Caruana, C.; Agius, A‐M.; Gainza‐Cirauqui, M. L.
Abstract: Introduction: Many societies have observed a steady increase of many older adults living longer due to advancements in health and standard of living. The dental team requires specialised training in gerodontology to better prepare for the future needs of the elderly patients. It is the aim of this study to report the undergraduate students' activities and perspectives on their work experience in a geriatric residence. Materials and Methods: An anonymous online questionnaire on the theoretical and practical aspects of training was sent to students in dentistry and dental hygiene (DH) undergraduate courses. Students were also invited to discuss their experiences. Data of clinical treatment performed by the students were collected. The number of clinical hours of student exposure to patients was measured. Results: Completion of the questionnaire was high (90%). Both DH and dentistry students have in excess of 100 hours/y of clinical practice. Overall students rate their experience as a positive one that enriches patients' well‐being. However they identify barriers to oral health and experience challenges related to their clinical work and level of competence (Kruskal‐Wallis Test P < .05). Conclusions: study participants were strongly motivated towards the management of frail older adults and cognisant of the barriers and constraints of achieving a reasonable level of oral health. Gerodontology programmes should be adaptable in order to create the appropriate environment and address socio‐emotional challenges experienced by students.